The Hip Hop Music in the United States of America during the 1970’s: A Means to Call for Equality - KHELIFA, Fatima (My University, 2020)
Africans lived many centuries in pursuit of freedom. In America, they struggled not to be considered inferior and are still segregated. For this reason, the conditions of the African Americans helped them launch political and cultural movements to call for their rights. Music was a means used by them as a protest against inequality and injustice. The present dissertation attempts to show how the Hip Hop music contributed to spreading the voices of the African Americans that call for freedom and condemn the racial discrimination in the USA. The study starts by providing an overview of the slavery conditions in America. It also presents the major social and cultural activities of the African Americans during the 20th century.
Keywords: Hip Hop; African Americans; Racism; Segregation